Perbandingan Kinerja Keuangan PT Inalum Sebelum dan Sesudah Akuisisi PT Freeport Indonesia Melalui Pendekatan Economic Value Added - Linda Sri Mulyati; Djoni Djatnika; Fifi Afiyanti Tripuspitorini (Indonesian Journal of Economics and Management, 2021)
This research to see the ratio of financial performance of Inalum before and after the acquisition of Freeport Indonesian through the EVA approach for the 2013-2020 period. Financial reports as material for analysis obtained from the website of Inalum and SGX with the type of data, quantitative and secondary data. The data analysis technique used is to assess financial performance using a comparative analysis of the EVA approach from 5 years before and 3 years after the acquisition with the data analysis instrument used NOPAT, WACC, and IC. From the results, financial performance is not good because the company has a negative EVA every year. This shows that the profits have not been able to cover the cost of capital. After the acquisition, the EVA value generated by the negative company is greater than the before the acquisition, so the company's financial performance before is better than after the acquisition.